Instagram Live (IG Live) sebagai Sarana Sosialisasi Layanan Pustaka Perpustakaan Universitas Gadjah Mada di Masa Pandemi Covid-19 - Sarwono; Maryono; Saptari, Janu (Perpustakaan Universitas Gadjah Mada, 2023)
This paper aims to describe Instagram Live (IG Live) as socialization program at UGM Library during Covid-19 pandemic. One of the duties and functions of the library is to socialize library services which aims to provide library services information. Library services socialization at UGM Library is usually carried out through literacy or library education programs where users attend scheduled class. During the pandemic, social and physical distancing was in effect so that socialization was packaged using social media. One of the popular social media platforms used is IG Live. This article analyzed IG Live as a means of socialization of library services at UGM Library during the pandemic. A qualitative descriptive form with data collection techniques through observation, direct participation, and documentary study is used to describe the research phenomenon. The results show that the information conveyed includes: 1) health and safety; 2) facilities and services; 3) procedures of circulation service; 4) access of the collections; and 5) email/contact person of library services. The various interesting and interactive features in IG Live can be used as a consideration for using this facility to socialize library activities.